Die Register Innocenz' III. 13. Jahrgang (1210/1211). Texte und Indices - Sommerlechner, Andrea (Verlag der Österreichischen Akademie der Wissenschaften, 2015)
The volume is containing the critical edition of 207 letters of pope Innocent III' addressed to recipients all over Europe and in the Middle East which were entered into the chancery registers of the 13th year of pontificate (1210/1211). It is the first of four volumes transmitted not as original but as a copy written at the Curia in mid-14th century and as print published in the 17th century.